Effective parameters for conductive contributionsto radial heat transfer in fixed beds under stagnantconditions - Suárez, Felipe (2017)
New expressions to evaluate the thermal conduction parameters in fixed beds of monosized spheres are presented in this paper. The parameters are those introduced by the 2R2D model proposed by Asensio et al. (2014): the effective thermal conductivity for the solid core of the bed λes,c​ a heat transfer coefficient between the first layer of particles and the wall surface hwp and a heat transfer coefficient between the first layer of particles and inner particles hpL. For a better comparison with experimental data those properties are readily associated with the corresponding parameters for stagnant beds λ0 e, c, h0 wp and h0 pL. Expressions to evaluate the three thermal parameters have been developed on common bases, consisting of a precise approximation for the confluence of flux lines in the particles towards the contact points and packing properties evaluated independently. It is shown that the coefficient h0 pL can be directly expressed in terms of λ0 e, c,; therefore the practical number of conduction parameters are effectively reduced to λ0 e, c, h0 wp and h0 pL. The results from the expressions proposed here for λ0 e, c, h0 wp and h0 pL have been compared with experimental data without employing any fitting parameter. In either case, the analysis of the estimations for particles of nearly spherical shapes did not reveal significant systematic deviations. Experimental information at conditions outside the framework of the theoretical development, such as for rarefied gases and particle shapes other than spherical, was also considered. The analysis of these cases was helpful in assessing effects requiring additional extensions